Generation of 16 Micrometer IR Laser by theOptical Pumping of CF4 Gas Molecules (Baghdad Science Journal, 2025)
We report here the observation of 16 µm superradiance laser action generated from optical pumping of CF4 gas molecules (which is cooled to 140 Kº by a boil-off liquid-N2) by a TEA-CO2 laser 9R12 line. Output laser pulses of 7 mJ and 200 ns have been obtained.